Comparison of anthropometric indices for the screening of nonalcoholic fatty liver disease in pre- and postmenopausal women. Issue 1 (January 2020) - Hong, So-hyeon; Hwang, Soon Young; Kim, Jung A.; Lee, You-Bin; Roh, Eun; Kim, Nam Hoon; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Choi, Kyung Mook; Baik, Sei Hyun; Yoo, Hye Jin
Abstract: Objectives: Although it has been well-established that menopause causes a shift in body fat, there has been no study conducted yet to examine the best obesity parameters to predict the risk of nonalcoholic fatty liver disease (NAFLD) in this population. Thus, the aim of this study was to clarify the superiority among various obesity indices such as body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) for predicting NAFLD in pre- and postmenopausal women. Methods: This cross-sectional analysis included 620 healthy women (318 premenopausal and 302 postmenopausal women) between 20 and 80 years of age recruited from the Health Promotion Center of Korea University Guro Hospital. NAFLD was diagnosed by abdominal ultrasonography. Results: In premenopausal women, there were no statistical differences in the area under the curve values among the three obesity indices, whereas, in postmenopausal women, the area under the curve value of WHR was significantly larger than those of either BMI (difference between area: 0.102, 95% confidence interval: 0.031, 0.173) or WC (difference between area: 0.064, 95% confidence interval: 0.018-0.109). Furthermore, in postmenopausal women, the combination of WHR with BMI or WC significantly increased predictive power of NAFLD when compared to using BMI or WC alone. The optimal cutoff values for BMI, WC, and WHR for detecting NAFLD were 23.9 kg/m 2, 69 cm, and 0.81 in premenopausal women and 22.9 kg/m 2, 74 cm, and 0.86 in postmenopausal women, respectively. Conclusions: In premenopausal women, BMI, WC, and WHR hold similar potential in predicting the risk of NAFLD, whereas, in postmenopausal women, WHR is the most useful discriminative indicator for NAFLD. Women's optimal cutoff values for NAFLD were different according to menopausal status. Abstract : Supplemental Digital Content is available in the text